Comparative Evaluation of Physical Properties of Conventional Glass Ionomer Cement with Different Additives: An In- vitro Study - Dr. Krina Gurjar; Dr. Shraddha Chokshi; Dr. Zarna Sanghvi; Dr. Pooja Joshi; Dr. Purav Mehta; Dr. Ronak Choudhary (The Bioscan, 2025)
Aim: This study aimed to evaluate and compare the Physical properties of Type IX Glass ionomer cement (GIC) incorporated with 2% chlorhexidine (CHX) and 2% cetrimide. Settings and Design: An in-vitro comparative study Material and Methods: The study comprised six test groups - Group 1 (Conventional GIC), Group 2 (GIC + 2% CHX), and Group 3 (GIC + 2% cetrimide). Each group contained 15 samples, which were evaluated for microleakage using dye penetration test. Class I cavity was prepared in all the samples and were restored with experimental GICs. CHX and cetrimide in powder form were added to conventional Type IX GIC at 2% W/W ratio. Thermocycling was done and dye penetration test was performed. Samples were sectioned and were evaluated for microleakage under stereomicroscope. Group 4 (Conventional GIC), Group 5 (GIC + 2% CHX), and Group 6 (GIC + 2% cetrimide) were evaluated for Compressive strength using universal testing machine. Kruskal–Wallis test complemented by Tukey’s post-hoc test and intragroup comparison was made by Student’s paired t-test for the comparative analysis of both microleakage and evaluation of compressive strength between the three experimental type IX GICs. Result: Group I showed least microleakage, Group 4 showed highest mean compressive strength. Conclusion: The present study demonstrated that experimental GICs containing CHX and cetrimide, increased the microleakage and decreased the compressive strength of the parent material.